Konsekuensi Hukum Ketiadaan Standar Kompetensi Pimpinan Alat Kelengkapan DPRD - Akbar Nugraha Pangayoman; Fauzi Syam; Arfa'i Arfa'i (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study analyzes the regulation of the appointment of leaders of DPRD supporting bodies and the legal consequences of the absence of educational qualifications or competency standards. The research problem focuses on whether a mechanism based on factional representation, proportionality, and internal political agreement provides objective criteria for assessing eligibility for office. This normative legal research applies statutory and conceptual approaches. The findings show that positive law regulates the formation of DPRD supporting bodies and the mechanism for filling leadership positions, but does not establish minimum competency parameters for those positions. The novelty of this study lies in positioning this normative gap as an institutional legal problem rather than merely an internal political issue of the DPRD. This condition affects legal certainty, objectivity in eligibility assessment, institutional professionalism, and the quality of local legislation, budgeting, oversight, and ethical enforcement. The study recommends proportionate competency-based regulation through DPRD rules of procedure, task orientation, training, certification, and performance evaluation without restricting the political rights of DPRD members.